Mathematical Model for Searching for an Optimal Solution to the Problem of Forming Supply Chains for Raw Materials of Forestry Enterprises under Conditions of Uncertainty - R. S. Rogulin (Управленческие науки)
This paper examines important aspects related to the problems of forming supply chains and production volumes at forest processing enterprises. The main emphasis is on assessing the optimality of decisions made. The study focuses on enterprises that do not have their own sources of raw materials and that are seeking to find the most appropriate solution based on the planning horizon based on data on transactions carried out on the commodity exchange. The purpose of the study is to create a mathematical model that allows us to establish the optimal volume of production of goods based on the formed supply chains of raw materials from the commodity exchange, considering the share of its useful volume, the time the lots are in transit and the uncertainty associated with supply and logistics. The following research methods were proposed: mathematical modeling, theory and optimization methods. Testing the model using data from the St. Petersburg Stock Exchange and enterprises of the Primorsky Territory made it possible to determine the optimal trajectories of profit, production volume and other important indicators. The work also raises issues of planning supply chains and production volumes, analyzes regions – sources of raw materials and presents the advantages and disadvantages of the presented mathematical model. The results obtained are of interest to the top management of forestry enterprises seeking to improve the efficiency of their activities and can be the basis for assessing the rationality of commodity transactions on the Russian Commodity and Raw Materials Exchange.